ANALISIS EKSPOSUR RISIKO REKSADANA SYARIAH DAN REKSADANA KONVENSIONAL DI INDONESIA DENGAN PENDEKATAN CAPM, MARKET TIMING ABILITY DAN DOWNSIDE RISK - Mubasysyyratul Ummah Sapsuha (Institut Agama Islam Negeri (IAIN) Ternate, 2023)
This study was conducted to determine the risks of conventional mutual funds and sharia types of stocks in Indonesia during the period 2017-2021. Through this research, the public as potential investors, general investors, and investment managers will get information about the risk of mutual fund by comparing the results of risk, measurements of each mutual fund, considering the increasing number of mutual fund investment instruments of either type or number. The measurement methods used are capm beta value, beta market timing ability and beta downside (downside risk). The results showed that using these three measurements, the total risk exposure of Islamic mutual funds was lower than that of conventional mutual funds.